Rationale, completeness and quality of evidence for the use of ursodeoxycholic acid in neonatal hyperbilirubinemia - Olesya V. Zakharova (Педиатрическая фармакология)
Background. Systematic reviews are considered the highest evidence of the effectiveness and safety of treatment methods used in clinical practice. The veracity of a results and conclusions of systematic reviews is directly related to their quality. The aim of the study is an assessment of the currency, completeness and methodological quality of published systematic reviews on the evaluation of the effectiveness of ursodeoxycholic acid (UDCA) for the treatment of neonatal hyperbilirubinemia. Materials and methods. A meta-epidemiological methodological study was conducted. The search for evidence sources was performed in November 2023 in the specialized databases MEDLINE, Cochrane Central Register of Controlled Trials (CENTRAL), Cochrane Database of Systematic Reviews (CDSR), LILACS, CNKI, LENS.ORG, еLibrary.Ru, in registers ClinicalTrials.gov, ICTRP, ISRCTN, PROSPERO, as well as in the Google Academy and Google search engines. Additionally, the lists of references and citations of selected publications have been reviewed. Only systematic reviews and randomized clinical trials are included in the study. The search was carried out to assess the currency and completeness of systematic reviews. A systematic review is considered currency if the most recent studies are included in its analysis. A systematic review is considered complete if its analysis includes all identified studies that meet the inclusion criteria set by the review authors and are published no later than the date of the last search conducted by the review authors. The methodological quality of the systematic reviews was assessed using the AMSTAR-2 tool. Results. As a result of the search, 4 systematic reviews and 23 randomized trials were identified. All reviews evaluated the effect of UDCA in combination with phototherapy on the level of total serum bilirubin, the duration of phototherapy and the frequency of adverse events (for example, loose stools, vomiting, rash) compared with phototherapy alone and/or placebo. All systematic reviews have been published over the past two years, but have already lost their currency. There are missing studies and/or outcomes in each review. The methodological quality of the reviews was found to be extremely low. Conclusion. Given the listed shortcomings of systematic reviews, their results and conclusions should be treated with caution. In order to obtain the most accurate and reliable evidence, a new systematic review is needed.